Secure and Scalable Cyber-Physical Systems Architecture for Smart Factory Automation - Ahmed Alkilany; M. F. Bara (National Journal of Electrical Electronics and Automation Technologies, 2025)
Due to the high level of the rapid spread of the concept and technologies of Industry 4.0, the utilisation of Cyber-Physical Systems (CPS) as the key technology to build the smart factory automation was quickly adopted. But both scalability and robust security have been an urgent problem to be achieved in the mentioned systems because of the heterogeneous integration of devices, the great amount of data flow, and ever-more advanced cyber threats. The paper proposes a scalable and secure CPS architecture which will work in a smart factory setting. The suggested framework incorporates tiered security protocols, distributed cloud-edge computation and real-time standards interoperability to provide reliable operation in variable manufacturing environments. The most relevant innovations will be blockchain-based trust management which will ensure device authentication is decentralized, software-defined networking (SDN) which will facilitate dynamic resource allocation and federated learning-based anomaly detection so that privacy is not compromised but collaborative threat evasion is possible. The testbed was simulated smart factory built on Hyperledger Fabric, OpenDaylight SDN controllers, and edge computing nodes to measure the performance. The outcome has shown a 60-percent decrease in latency in the control loop and a 2.5-fold the increase in throughput along with the effective mitigation of 95 percent of the simulated cyber-attacks compared to a typical centralized architecture. These results indicate the potential of the proposed CPS design in achieving resilience, flexibility, and efficiency of operations and offer a viable way on safe and scalable smart manufacturing in the industry 4.0 where security is being prioritized.